Speech by Brig. Gen Dato’ Prof. Dr. Kamarudin Hussin Vice Chancellor of UniMAP for Opening Ceremony 25th Regional Conference on Solid State Science & Technology 2009 - Kamarudin, Hussin, Brig. Gen. Dato’ Prof. Dr. (Universiti Malaysia Perlis, 2010)
Event was held at Bayview Beach Resort, Penang, Malaysia.